TRANSMISI LEGONG DALAM PARADIGMA SEKULARISASI DI BALI (Widyadari : Jurnal Pendidikan, 2021)
The transmission of legong dance in Bali in this study is a transformation from a ritual (sacred) legong dance to a Balinese-balihan (secular) art. The purpose of this study is to describe and analyze dance transmission as an impact of community development. Research on the transmission of legong dance in the secularization paradigm is to increase people's understanding of art as a cultural heritage inherent in Balinese life, both physically and mentally. This research is very important to do to provide an understanding to the community that the legong dance contains cultural values ​​that can function to shape social attitudes and behavior in accordance with Hindu culture and religion in Bali. The transmission process of the legong dance is one of the efforts to preserve culture, so that the legong dance of cultural heritage does not become extinct. The methodology as the basis for data collection uses qualitative research methods and the analytical tool is the theory of secularization. To understand the existence of the seculararization process, structural functional theory is used. The results of this study indicate that the background of legong in Bali, originally a sacred art as the creativity of devotion in religious ceremonies, has developed into a spectacle art which has implications for the development of various pelegongan creations which have become the attraction for the younger generation, nowadays.